Pengaruh Entrepreneurial Competency dan Financial Literacy terhadap Business Performance Sustainability melalui Inovasi sebagai Variabel Mediasi pada UMK Sektor Kuliner di Kota Jambi - R, Dzaky Achmad; Setiawati, Rike (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of entrepreneurial competency and financial literacy on business performance sustainability with innovation as a mediating variable. This study uses a quantitative approach with primary data obtained through questionnaires distributed to 100 MSMEs selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) through SmartPLS4, including validity and reliability testing, as well as hypothesis testing using the bootstrapping method. The results show that entrepreneurial competency has a positive and significant effect on business performance sustainability. In addition, entrepreneurial competency and financial literacy have a positive and significant effect on innovation. However, financial literacy does not have a significant effect on business performance sustainability. Other findings indicate that the innovation variable does not mediate the relationship between entrepreneurial competency and financial literacy with business performance sustainability. The implications of this study emphasize that entrepreneurial competency is a key factor that directly drives sustainable business performance, while financial literacy and innovation require more comprehensive strategic support to provide optimal contributions to business sustainability.